2015
DOI: 10.1080/19440049.2015.1077396
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of caffeine intake in the Korean population

Abstract: An improved method for the analysis of caffeine in foods by HPLC was validated by measuring several analytical parameters. The caffeine contents of 1202 products available from Korean markets were analysed. A consumption study was conducted by using data from the Korea National Health and Nutrition Examination Survey (KNHANES), 2010-12, to estimate the caffeine intakes of the Korean population. The mean intakes of caffeine from all sources in the general population and consumers were 67.8 and 102.6 mg day(-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
1
27
1
2
Order By: Relevance
“…Coffee consumption is one possible risk factor for bleeding in early pregnancy in the first trimester. Even though the market for caffeinated beverages has increased in the past decades, coffee remains the most frequently consumed caffeinated beverage [1,7]. A standard cup of coffee is generally expected to provide 100 mg of caffeine; however, this varies according to portion size, brewing method, and brand [1-3, 6, 7, 22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coffee consumption is one possible risk factor for bleeding in early pregnancy in the first trimester. Even though the market for caffeinated beverages has increased in the past decades, coffee remains the most frequently consumed caffeinated beverage [1,7]. A standard cup of coffee is generally expected to provide 100 mg of caffeine; however, this varies according to portion size, brewing method, and brand [1-3, 6, 7, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Although other beverages have some caffeine content (one cup of tea, 64.0 mg of caffeine; 12 oz. of coke, 46.0 mg of caffeine; one cup of hot chocolate, 16.0 mg of caffeine; and caffeinated soda, 46.0 mg of caffeine), these caffeinated beverages do not significantly affect daily caffeine consumption among Koreans [7,23]. Nisenblat et al reported that caffeine intake is not associated with an increased risk of bleeding in early pregnancy, with the possible exception of very high levels of caffeine intake [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeine, theobromine, theophylline, and pentoxifylline are derivatives of methylxanthine. While the majority of caffeine consumption comes from coffees, teas, and colas (Lim et al ., ), other sources include supplements, energy drinks, and chocolate. Theobromine is found in chocolate, tea leaves, and the cola nut.…”
Section: Alcohol Tobacco and Drugsmentioning
confidence: 99%
“…The EU requires a 'high caffeine content' label for products with caffeine in excess of 150 mg [28]. The US FDA does not require the amount of caffeine be displayed but caffeine must be listed as a product [29]. Recently, the Korean National Food and Drug Administration implemented a new requirement of labeling the total amount of caffeine in products including café-made coffee in order to prevent caffeine overdose [5].…”
Section: Introductionmentioning
confidence: 99%